Job Equalization Policy Implementation and Competency Development of Civil Servants: A Case Study of Policy Analysts in East Manggarai Regency - Ahyar Ahyar; Raniasa Putra; Muhammad Abduh (ARISTO, 2026)
This study investigates the implementation of the job equalization policy and the development of civil servant competencies in East Manggarai Regency, with a focus on the functional position of policy analysts. The research is motivated by concerns that the nationwide conversion of structural positions to functional ones, while administratively mandated, may not be accompanied by adequate competency development, particularly in under-resourced regions. Employing a qualitative case study design, the study collected data through interviews, document analysis, and field observations, and analyzed the findings using thematic coding supported by Edwards III’s implementation model, Kingdon’s Multiple Streams Framework, and Spencer’s competency theory. The results reveal that although structural transitions were formally implemented, the substantive preparation for new functional roles remains insufficient. Communication was top-down and unclear; training opportunities were severely limited; and performance indicators were misaligned with functional responsibilities. Most policy analysts lacked the technical and behavioral competencies required for their roles, resulting in diminished organizational performance and weakened public service outcomes. The absence of institutional support mechanisms, such as mentoring and performance benchmarks, further hindered adaptation and professional growth.The study concludes that successful implementation of job equalization policies requires more than administrative compliance—it demands strategic investment in human capital, institutional learning, and localized policy adaptation. This research contributes to public administration literature by illustrating how structural reforms must be paired with competency development to realize their intended impact, especially in decentralized, capacity-constrained environments. Keywords: Job Equalization Policy; Policy Analyst; Competency Development; Public Sector Reform; Implementation; Bureaucratic Transformation;